Increased occurrence of liver and gastrointestinal diseases and anaemia in women with Turner syndrome – a nationwide cohort study. Issue 7 (7th February 2021) - Viuff, Mette Hansen; Stochholm, Kirstine; Grønbæk, Henning; Berglund, Agnethe; Juul, Svend; Gravholt, Claus Højbjerg
Summary: Background: Liver and gastrointestinal diseases are frequent in women with Turner syndrome. However, their association with bleeding disorders, anaemia and the impact of hormone replacement therapy is unknown. Aims: To investigate the risk of liver and gastrointestinal diseases, haemorrhage and anaemia in women with Turner syndrome compared with the female background population, and the long‐term impact of hormone replacement therapy on these conditions. Methods: One thousand one hundred and fifty‐six women with Turner syndrome diagnosed during 1960‐2014 were identified using the Danish Cytogenetic Central Registry and linked with personal‐level data from the National Patient Registry and the Medication Statistics Registry. Statistics Denmark randomly identified 115 577 age‐matched female controls. Negative binomial regression was used to analyse hospital discharge diagnoses. Medical prescriptions, mortality and the effect of hormone replacement therapy were estimated using stratified Cox regression. Results: Liver disease increased 13‐fold (IRR 12.9 (95% CI 5.8‐28.8)), due to toxic liver disease (IRR 8.0 (95% CI 1.8‐35.4)), liver insufficiency (IRR 6.7 (95% CI 1.7‐26.9)), fibrosis/cirrhosis (IRR 16.5 (95% CI 2.2‐122.1)) and unspecified liver disease (IRR 10.6 (95% CI 4.4‐25.3)). Furthermore, presence of abnormal liver enzymes increased 12‐fold (IRR 12.4 (95% CI 4.2‐36.6)). The risk of gastrointestinal haemorrhage (IRR 3.4 (95% CI 1.8‐6.2)), anaemia (IRR 3.2 (95% CI 2.0‐5.0)) and coagulation disorders (IRR 2.9 (95% CI 1.1‐7.1)) was increased. However these diagnoses were not associated with inflammatory bowel disease. Gastrointestinal mortality was increased three‐fold (HR 3.1 (95% CI 1.5‐6.2)), partly due to death by liver disease (HR 3.0 (95% CI 1.1‐8.2)), gastrointestinal haemorrhage (HR 29.6 (95% CI 3.1‐285.1)) and capillary malformations (HR 18.6 (95% CI 4.1‐85.0)). There was no effect of hormone replacement therapy on gastrointestinal risk but a trend towards a beneficial impact on liver diseases. Conclusions: The risk of being diagnosed with liver disease was higher than previously reported. The occurrence of gastrointestinal haemorrhage and anaemia was increased in Turner syndrome. There was no effect of hormone replacement therapy on gastrointestinal risk but a trend towards a beneficial impact on liver diseases was detected. Abstract : Turner syndrome women have a substantial risk of being admitted with gastrointestinal disorders. In particular inflammatory bowel disease, liver disease, coeliac disease, gastrointestinal hemorrhage and anemia. Furthermore, their risk of dying from gastrointestinal disease is three‐fold increased.